The chromosome-level genome of Eucommia ulmoides provides insights into sex differentiation and α-linolenic acid biosynthesis - Du, Qingxin; Wu, Zixian; Liu, Panfeng; Qing, Jun; He, Feng; Du, Lanying; Sun, Zhiqiang; Zhu, Lili; Zheng, Hongchu; Sun, Zongyi; Yang, Long; Wang, Lu; et al. (Frontiers in Plant Science, 2023)
Eucommia ulmoides Oliver is a typical dioecious plant endemic to China that has great medicinal and economic value. Here, we report a high-quality chromosome-level female genome of E. ulmoides obtained by PacBio and Hi-C technologies. The size of the female genome assembly was 1.01 Gb with 17 pseudochromosomes and 31,665 protein coding genes. In addition, Hi-C technology was used to reassemble the male genome released in 2018. The reassembled male genome was 1.24 Gb with the superscaffold N50 (48.30 Mb), which was increased 25.69 times, and the number of predicted genes increased by 11,266. Genome evolution analysis indicated that E. ulmoides has undergone two whole-genome duplication events before the divergence of female and male, including core eudicot γ whole-genome triplication event (γ-WGT) and a recent whole genome duplication (WGD) at approximately 27.3 million years ago (Mya). Based on transcriptome analysis, EuAP3 and EuAG may be the key genes involved in regulating the sex differentiation of E. ulmoides. Pathway analysis showed that the high expression of ω-3 fatty acid desaturase coding gene EU0103017 was an important reason for the high α-linolenic acid content in E. ulmoides. The genome of female and male E. ulmoides presented here is a valuable resource for the molecular biological study of sex differentiation of E. ulmoides and also will provide assistance for the breeding of superior varieties.